Indigenous teachers in the south of Brazil: from domination/submission contexts to the paths of autonomy - Maria Aparecida Bergamaschi; Cláudia Pereira Antunes (FahrenHouse, 2020)
This paper mainly tackles the training of Kaingang teachers in the south of Brazil. Methodologically funded on cartographical perspective, the study intends to show a historical movement that gradually breaks through the domination and tutelage practices enforced upon native people. Initiated by the Portuguese colonization, the domination practices were extended and deepened throughout the whole colonial period and specially on the 20th century, when the Brazilian government created more effective mechanisms for integrating the indigenous population into the national society, being among them the school education. Although the domination/subordination process has caused many damages to the autonomous existence of each indigenous community, we point out that there was also a strong, even if sometimes silent process of re-existence (resistance/re-existence), that became more evident and reverberant in the last two decades of the 20th century and during the 2000's. The documental registries and historiographical studies here analyzed highlight the coy and sporadic state initiatives, in frequent agreement with religious orders, in the educational training of Kaingang teachers for the schools built in the indigenous lands. Changes begin to occur as of the Federal Constitution of 1988, that officially abolished the integration-seeking school education and tutelage, and legally supported the indigenous demands for a specific school, with teachers who belong to their people. In consequence, we see protagonist and autonomous indigenous acts, breaking the tutelary practices deployed under domination/submission contexts, and opening paths for autonomy concerning specific school education and indigenous teachers' performance.